Enhanced luminescence of Mn4+-activated CaAl12O19 red phosphors by synergetic manipulation of the flux effect and charge compensation for warm WLEDs application - He, Youyi; Liu, Jun; Gao, Yalei; Yan, Lijuan; Lv, Fengzhen; Liu, Fuchi; Long, Lizhen (Journal of materials science. Materials in electronics, 2021)
Mn 4+ -activated phosphors have become a hotspot in the development of inorganic red phosphors due to the fascinating photoluminescent properties. Herein, the synergetic manipulation of the flux effect and charge compensation was employed to improve the performance of Mn 4+ -activated CaAl 12 O 19 red phosphors. The crystallinity was improved by appropriate Zn 2+ -doping, while nonradiative transition between Mn 4+ ions is reduced by charge compensation of the formation of Mn 4+ –Mg 2+ pairs with Mg 2+ dopants. Thus, the emission of Mn 4+ -activated CaAl 12 O 19 red phosphors has been remarkably enhanced. The low probability of nonradiative transition between Mn 4+ ions was demonstrated by the thermal stability analysis. To depict the luminescent process, the crystal-field strength ( D q ), and Racah parameters ( B and C ) were calculated to determine the sequence of the energy levels. Meanwhile, the warm WLEDs with high CRI and low CCT were obtained using the prepared phosphors as red-emitting composition. Our results clearly suggested that the synergetic strategy by combining the flux effect and charge compensation is an effective method to enhance the luminescence of CaAl 12 O 19 :Mn 4+ , and CaAl 12 O 19 :Mn 4+ /Zn 2+ /Mg 2+ red-emitting phosphors, which have potential application value in warm WLEDs.